bahasa inggris - Indri Margaretha; Duano Sapta Nusantara; Rohati Rohati (Universitas Muhammadiyah Metro, 2026)
Despite the growing integration of Artificial Intelligence (AI) in education, there remains a critical gap in research that specifically synthesizes how AI tutors interact with diverse learning styles to influence students' numeracy literacy. Previous studies tend to address AI in education or learning styles in isolation, without examining their intersecting effects on numeracy outcomes. This study aims to map the profile of students' numeracy literacy across learning styles when using an AI tutor, analyze student interaction patterns with AI tutor features, and identify factors influencing numeracy literacy outcomes. A Systematic Literature Review (SLR) was conducted following PRISMA guidelines, analyzing 14 peer-reviewed articles published between 2018 and 2025 from Scopus and ScienceDirect databases. Bibliometric analysis using VOSViewer identified four conceptual clusters with